HUBUNGAN HIGIENE PERORANGAN DAN SANITASI LINGKUNGAN DENGAN KEJADIAN DEMAM TIFOID DI DESA AIR PAOH WILAYAH KERJA UPTD PUSKESMAS SUKARAYA TAHUN 2023 - Ani Pitria Dewi; Eko Heryanto; Arda Suryadinata (Jurnal Ilmiah Medsains, 2023)
Based on data on the 10 most common diseases at the UPTD Puskesmas Sukaraya in 2022, the clinical examination found typhoid fever cases of 1,001 cases (26.1%). Air Paoh Village which is in the UPTD Puskesmas Sukaraya Working Area with the highest cases of typhoid fever. Recorded in 2022 as many as 342 cases (8.9%). This study aims to determine the relationship between personal hygiene and environmental sanitation with the incidence of typhoid fever in Air Paoh Village in 2023. The research design used Cross Sectional. The population was all mothers in Air Paoh Village totaling 2,275 mothers with a total sample size of 97 respondents. The statistical test used is the chi square test. The results of bivariate analysis obtained the variable results of hand washing habits with a p value of 0.008, the habit of washing raw food ingredients with a p value of 0.000, clean water facilities with a p value of 0.000, latrine conditions with a p value of 0.000 and the provision of trash cans with a p value of 0.000. There is a significant relationship between the habit of washing hands, the habit of washing raw food ingredients that are directly eaten, clean water facilities, latrine conditions, provision of trash bins with the incidence of typhoid fever in Air Paoh Village.